Efecto de dietas con distinto contenido de fibra en el peso y grasa corporal en ratones BALB/c inducidos a obesidad - Martínez Haaker, Marisa Elisa (2013)
Introduction: Fiber is a type of carbohydrate resistant to digestion and absorption in the small intestine, which is partially or completely fermented in the large intestine. Beneficial physiological effects are attributed to it, including laxative effect, diminish of blood cholesterol, blood glucose regulation, among others. For these reasons, it could be useful in the treatment of overweight and obesity, which prevalence has increased significantly in the last years, with a consequent increment on body fat percentage in humans. Objective: Evaluate the effect of the intake of diets with different fiber content in weight, body fat percentage and stool weight in BALB/c mice induced to obesity. Design: Experimental study. Methods: 24 male BALB/c mice of eleven weeks of age which had been induced to obesity were studied. The mice were randomly distributed into 4 groups of 6 each and were fed with diets containing different amounts of fiber during 4 weeks. Body weight, stool weight and food intake were evaluated on a daily basis. After the 4 weeks of experiment the mice were sacrificed in order to measure the body fat percentage. Results: A non significant increase in weight was noted in mice that ingested higher fiber content diets (p-value = 0,363). However, there was a significant increase in volume of stool in mice that ingested higher fiber content diets (p-value = 0,004), finding statistical significance between the group Little DF and the other groups, as well as between the group Regular DF and Very high DF (p-value < 0,001). Regarding body fat percentages, no specific decrease pattern was observed. In relation to the body fat percent, no specific decreasing patron was observed. Conclusion: The intake of dietary fiber has beneficial effects in body and stool weight in BALB/c mice induced to obesity. A higher intake of dietary fiber results in less body fat increase and in a higher volume of feces. A maximum beneficial content of dietary fiber in diets was determined (4,52%). There was no statistical significance between the medias of body and stool weight of the mice from groups High DF and Very high DF. No relation was found between the body fat percentage and the amount of fiber ingested by male BALB/c mice.